Alcohol and drug use among road users involved in fatal crashes in Norway. (21st April 2021) - Pasnin, Live Tanum; Gjerde, Hallvard
Abstract: Objective: To study the prevalence of alcohol and drugs in biological samples from drivers, motorcycle riders, bicyclists, and pedestrians involved in fatal road traffic crashes (RTCs) during 2016-2018 in Norway, both among fatally injured victims and those who survived fatal RTCs. Methods: Anonymous information was extracted from police data. No personal data were recorded. Results: There were 330 fatal RTCs with 349 killed road users and 384 survivors during the study period; this included 179 passengers who were excluded from the study. In total, 90% of the studied killed road users and 67% of the survivors were investigated for alcohol or drug use by analyzing biological samples. Alcohol or drugs in concentrations above the legal limits were detected in 21% of the analyzed samples. The proportion impaired by alcohol or drugs (blood alcohol concentrations equal to or greater than 0.05%, or drug concentrations above equivalent limits) was highest among killed bicyclists (43%), higher than among killed pedestrians (24%), car and van drivers (28%) and motorcyclists (20%), and significantly higher than among drivers who survived fatal crashes (4%). Conclusions: Impairment due to use of alcohol or drugs was often a contributing factor among bicyclists, pedestrians and motor vehicle drivers who died in RTCs. Driving under the influence of alcohol or drugs was more often a contributing factor in cases where the motor vehicle driver was killed than in cases where the driver survived.